IgG antibodies in early Pseudomonas aeruginosa infection in cystic fibrosis. Issue 6 (June 1992) - Cordon, S M; Elborn, J S; Rayner, R J; Hiller, E J; Shale, D J
Abstract : The relationship between IgG antibodies to Pseudomonas aeruginosa and its isolation from sputum was determined in 100 patients with cystic fibrosis observed at intervals of two months for a median period of one year. Only one patient had a raised antibody titre (greater than 22.9 ELISA units) before isolation of P aeruginosa. Initially 65 patients were antibody negative, of whom 48 were also culture negative. Of 24 patients with positive sputum culture and negative antibodies, seven became antibody positive at a median (range) 15 (6-25) months later. The remaining 17 patients continued antibody negative until the end of the study at a median range 15 (1-123) months after becoming culture positive. This latter group were younger and had more intermittently positive sputum cultures. In general positive IgG antibody titres do not predate isolation of P aeruginosa, but in some patients are present soon after acquisition of infection. A positive titre indicates significant exposure to P aeruginosa and could be used to detect infection in patients unable to produce sputum and possibly indicate the effect of early antipseudomonal treatment.